The Determinant Factors of Company Value in Consumer Non-Cyclicals Companies: Two Pathways Analysis - Napisah, Napisah; Widiyati, Dian; Nurhayati, Nurhayati (CV. Ulil Albab Corp, 2026)
The objective of this study is to examine the impact of capital structure, good corporate governance, audit quality, and integrated reporting on firm value in consumer non-cyclicals enterprises listed on the Indonesia Stock Exchange from 2019 to 2023. A company's firm value is a key indicator of its sustainability, potential for growth, and appeal to investors. Capital structure is measured by the debt-to-equity ratio, and GCG is represented by the board of directors, independent commissioners, and institutional ownership. Public Accounting Firm reputation is used to evaluate audit quality, whereas disclosure ratings on sustainability and strategic reporting components are used to evaluate integrated reporting. This study makes use of panel data regression analysis, a kind of associative quantitative research. Firm value is positively affected by several factors, according to the research. These factors include capital structure, institutional ownership, independent commissioners, audit quality, and integrated reporting. In contrast, the board of directors does not have a significant effect. These findings support signaling theory and agency theory, indicating that companies with optimal capital structures, strong corporate governance mechanisms, high audit quality, and transparent integrated reporting are more likely to attract investors and enhance market valuation.